PENGARUH CUSTOMER EXPERIENCE TERHADAP CUSTOMER SATISFACTION PADA PASIEN RAWAT INAP KELAS VIP DI RUMAH SAKIT IMMANUEL BANDUNG - Yunus, Novita Wulansari; Aribowo, Agus (Majalah Ilmiah UNIKOM, 2020)
The purpose of this study was to determine the effect of customer experience on customer satisfaction in VIP class inpatients at Immanuel Hospital Bandung. Customer experience is measured through the dimensions of environment, convenience, competence, helpfulness. Customer satisfaction is measured through the dimensions of performance, reliability, and service ability. The method used in this research is descriptive method with quantitative and qualitative approaches. Descriptive method aims to provide an overview of the object of research based on the facts collected. The population is the patient and the patient's family at the Immanuel Hospital in Bandung. The sample of this study is inpatient service users of the VIP class Immanuel Hospital in the period of November 2019 - March 2020. In the study sample, researchers used the Slovin formula with a confidence level of 95% and an error rate of 5%, obtained a total sample of 170 people. Data analysis techniques using the classic assumption test was consisting of normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, partial test (t-test) based on significance value, simultaneous test (F-test) based on the significant value, and coefficient of determination analysis. The results showed a positive effect of customer experience on customer satisfaction in VIP class inpatients at Immanuel Hospital Bandung. Key Words : Customer Experience, Customer Satisfaction, Inpatient